Bioinformatic identification of Single Nucleotide Polymorphisms (SNPs) in candidate genes for fiber characteristics in alpacas (Vicugna pacos) - Fernández Suárez, Alvaro Gonzalo (2019)
The objective was to identify and predict the location of single nucleotide polymorphisms (SNPs) in genes related to fiber growth. The study was carried out with 31 keratin genes (KRT9, KRT12, KRT13, KRT14, KRT16, KRT18, KRT20, KRT25, KRT1, KRT3, KRT5, KRT6a, KRT6b, KRT6c, KRT7, KRT8, KRT71, KRT80, KRT31, KRT32, KIRT40, KRT81, KRT82, KRT10, KRT15, KRT17, KRT19, KRT2, KRT4, KRT79 y KRT83) associated with wool, fiber and hair characteristics in sheep, goat and human, respectively. These gene sequences were retrieved from the National Center for Biotechnology Information (NCBI) database. Using databases and bioinformatics tools such as the Conserved Domains database, Spling and Megablast, unique sequences for each gene were identified. These sequences were compared to the reference genomes: Vicugna_pacos-2.0.2 and Vi_pacos_V1.0 to identify single nucleotide polymorphisms (SNPs). In this manner, 48 SNPs were identified and localized in both intronic and exonic regions of 22 genes. We did not identify SNPs for KRT10, KRT15, KRT17, KRT19, KRT2, KRT4, KRT6b, KRT6c and KRT79. Comparative analysis among the four species studied allow to identify that sequences for KRT81, KRT6b and KRT6c genes are not present in the alpaca reference genomes. Similarly, genes KRT31, KRT14, KRT81, KRT83, KRT6b and KRT6c are not present in the ovine reference genome and, genes KRT31, KRT13, KRT81, KRT83, KRT6b and KRT6c are not present in the goat reference genome.